2021
DOI: 10.1002/ptr.7302
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol inhibits SARS‐Cov‐2 spike (S) protein‐induced cytotoxicity and inflammation through a PPARγ‐dependent TLR4/NLRP3/Caspase‐1 signaling suppression in Caco‐2 cell line

Abstract: Given the abundancy of angiotensin converting enzyme 2 (ACE-2) receptors density, beyond the lung, the intestine is considered as an alternative site of infection and replication for severe acute respiratory syndrome by coronavirus type 2 (SARS-CoV-2).Cannabidiol (CBD) has recently been proposed in the management of coronavirus disease 2019 (COVID-19) respiratory symptoms because of its anti-inflammatory and immunomodulatory activity exerted in the lung. In this study, we demonstrated the in vitro PPAR-γ-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In vitro studies have clearly demonstrated that SARS-CoV-2 infection activates the NLRP3 inflammasome in various cell types. SARS-CoV-2 S protein activates the NLRP3 inflammasome in Cacp-2 cells [ 24 ], and SARS-CoV-2 viroporin encoded by ORF3a triggers the NLRP3 inflammasome pathway in A549 cells [ 25 ]. In vitro studies of SARS-CoV-2-induced NLRP3 inflammasome activation have also been conducted in macrophages, human peripheral blood mononuclear cells (PBMCs), hematopoietic stem/progenitor cells (HSPCs), and endothelial progenitor cells (EPCs).…”
Section: Regulatory Roles Of Sars-cov-2 Infection In Inflammasome Ini...mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have clearly demonstrated that SARS-CoV-2 infection activates the NLRP3 inflammasome in various cell types. SARS-CoV-2 S protein activates the NLRP3 inflammasome in Cacp-2 cells [ 24 ], and SARS-CoV-2 viroporin encoded by ORF3a triggers the NLRP3 inflammasome pathway in A549 cells [ 25 ]. In vitro studies of SARS-CoV-2-induced NLRP3 inflammasome activation have also been conducted in macrophages, human peripheral blood mononuclear cells (PBMCs), hematopoietic stem/progenitor cells (HSPCs), and endothelial progenitor cells (EPCs).…”
Section: Regulatory Roles Of Sars-cov-2 Infection In Inflammasome Ini...mentioning
confidence: 99%
“… Types Roles Activators/inhibitors Models Ref. NLRP3 Activation SARS-CoV-2 spike protein Caco-2 [ 24 ] SARS-CoV-2 viroporin HEK293 & A549 [ 25 ] SARS-CoV-2 single-stranded RNA Macrophages [ 26 ] SARS-CoV-2 envelope protein BMDMs [ 27 ] SARS-CoV-2 nucleocapsid protein BMDMs & THP-1 [ 28 ] SARS-CoV-2 spike protein PBMCs [ 30 ] SARS-CoV-2 spike protein HSPCs & EPCs [ 31 ] SARS-CoV-2 spike protein HSPCs & EPCs [ 34 ] SARS-CoV-2 NSP6 Lung epithelial cells of COVID-19 patients [ 35 ] SARS-CoV-2 Blood cells of COVID-19 patients [ 37 ] SARS-CoV-2 Circulating monocytes of COVID-19 patients [ 38 ] SARS-CoV-2 Circulating monocytes of COVID-19 patients [ 39 ] SARS-CoV-2 spike protein BV-2 [ 42 ] SARS-CoV-2 Cerebral cortical tissues of COVID-19 patients [ 43 ] SARS-CoV-2 Aged COVID-19 patients [ 46 ] Inhibition SARS-CoV-2 NSP1 and NSP13 HEK293 & THP-1 [ 29 ] …”
Section: Regulatory Roles Of Sars-cov-2 Infection In Inflammasome Ini...mentioning
confidence: 99%
“…A recent finding has shown that CBD can reduce both the expression of ACE-2 and RhoA-GTPase/Caspase-1/NLRP3 signaling through its interaction with PPARγ in Caco-2 cells, as intestinal epithelium cells in vitro . This interaction leads to counteract the viral entry and viral replication in SARS-CoV-2 infection ( 33 ). CBD exerts its activity through the interaction with PPARγ in COVID-19 infection ( 4 , 33 ).…”
Section: Two Pathways Could Explain the Possible Actions Of Cbd In Sa...mentioning
confidence: 99%
“…This interaction leads to counteract the viral entry and viral replication in SARS-CoV-2 infection ( 33 ). CBD exerts its activity through the interaction with PPARγ in COVID-19 infection ( 4 , 33 ). PPARγ (peroxisome proliferator-activated receptor gamma) is a ligand-activated transcription factor which binds PPREs (PPAR-response elements).…”
Section: Two Pathways Could Explain the Possible Actions Of Cbd In Sa...mentioning
confidence: 99%
“…Recent articles have also highlighted the potential role of NLRP3-inflammasome in COVID-19. For example, studies have investigated the role of non-coding RNAs in the regulation of NLRP3-inflammasome complex in COVID-19, the relationship between NL-RP3-inflammasome and probiotics in COVID-19, the various aspects of inflammasomes as role players in COVID-19, and the potential role of the NLRP3-inflammasomes in COVID-19 [32][33][34][35][36][37][38][39][40][41]. Interestingly, a recent study has shown that specific suppression of the NLRP3-inflammasome represses the immune over-activation and diminishes COVID-19-like pathology in mice [42].…”
Section: Hyperactivity Of Nlrp3-inflammasome; a Key Factor In Covid-1...mentioning
confidence: 99%